The robustness of land equivalent ratio as a measure of yield advantage of multi-crop systems over monocultures. (13th January 2022) - Erickson, Richard; Deb, Debal; Dutta, Sreejata
Abstract: Land equivalent ratio (LER) is a most widely used indicator of yield advantage of multi-crop farms over sole-crop farms, and usually measured using crop biomass yield per unit area. Most often, crop yields are compared between both systems using the same area. In this paper, we demonstrate that although the yield per unit area and the yield per plant are widely different, LER remains invariant. As a corollary, area time equivalent ratio and land use efficiency, derived from LER, also remain unchanged when using the two different measures of crop yields. We recommend that when the estimation of the exact land area is difficult due to complex crop planting designs, yield per plant estimate is much easier and equally valid for estimation of LER and its derivative indices.